Educating to Forgive as an Expression of Concern for Order in a Person’s Natural Environment. Part 2: The Need for Forgiveness and its Effects - Wyrostkiewicz, Michał (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The paper describes the question of forgiveness and its importance in the process of the integral development of the human person. After earlier perceiving and accepting these anthropological premises, we can think of forgiveness as a necessity. The foundations of such thinking are two basic premises. The first of these is the belief in the inevitability of mistakes, therefore, potentially blaming other people. These faults and, on the other hand, harm suffered, disrupt proper interpersonal relationships, and returning to them is possible only through the act of forgiveness. The second premise is the natural need for justice, which is the realization of the naturally desired good by man. The forgiveness should be included into everyone's agenda and be presented as an imperative whose implementation is a condition of one's development, and the initial condition for order in a social environment